AN ANALYSIS THE LARGER PATTERNS IN THE REPORT TEXT ABOUT UNIVERSE - Dicky Kurniawan; Intan Satriani (IKIP Siliwangi, 2022)
This research is aimed to know about what larger patterns are used in the report text and what is the role of larger patterns used for the reader. This pattern, in which a general description is followed by more detailed descriptions with specific information, These patterns are describe something in general at the beginning and then explain in more detail about the information. General-specific patterns can be found in the encyclopedia and other reference texts, when someone will explain an event, surely they will tell their history widely in advance, information about it certainly comes from a reliable source so that the storyline can still be given to the public, general-specific is a way to explain a storyline from the beginning to the point. The Writer suggests the further researcher to use other more interesting sources to find more the larger patterns and to know about the role of the patterns. Keywords: Larger Patterns, Report Text, General-Specific